Faktor-faktor yang Berhubungan dengan PMBA serta Status Gizi Baduta di Desa Oeltua Kabupaten Kupang - Johanesta Novianti Belang; Anna Henny Talahatu; Sarci Magdalena Toy (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Kupang Regency is in the fourth position of incidents stunting the highest is in East Nusa Tenggara Province. Data measuring nutritional status in Oeltua Village in 2022 shows that it is 38.4% of children under five underweight, amounting to 18.1% of children under five stunting, and 15.4% toddlers wasting. Infant and young child feeding behavior (IYCF) in Indonesia to reduce stunting rates and improve quality of life according to targets SDGs also still low. This study aims to determine factors related to infant and child feeding practices and the nutritional status of toddlers in Oeltua Village, Kupang Regency. Data analysis used calculations Rank-Spearman. This type of research is an analytical observational approach cross sectional and the sample size was 76 mothers.  The research found that there are two variables that have a significant relationship with IYCF: maternal knowledge (p=0.025) and maternal education (p=0.000). Additionally, there are two variables that do not have a significant relationship with IYCF, namely household income and mother’s job. Feeding infants and children has a significant relationship with nutritional status (p=0.016). Advice to health workers to provide more education to mothers, especially regarding feeding according to age standards, and the risks of giving early complementary feeding.